IMPLEMENTASI PENDIDIKAN INKLUSIF BAGI ANAK USIA DINI - Nuraidah Nuraidah; Rusmayadi Rusmayadi; Muhammad Akil Musi; Abd Halik (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This research is a qualitative descriptive research that aims to determine the implementation of inclusive education in early childhood kindergartens. The subjects in this study are school principals, educators and students. The research procedure is carried out through the pre-field stage, the field work stage, and the data analysis stage. The data collection technique uses observation, interview and documentation techniques. The technique of checking the validity of the data uses triangulation. The data from the research results provide an overview of the Implementation of Inclusive Education in Early Childhood Kindergarten, starting with the identification of ABK through screening activities, classification, learning planning and monitoring of learning progress through MPLS activities. Preparation of assessments of cognitive, language and communication, motor, and perception development. Develop an individualized learning program by assessing the strengths, weaknesses, interests and needs of children from various aspects of development, developing long-term goals and short-term goals, designing methods and procedures for achieving goals and determining evaluation methods. Teachers implement an inclusive PAUD curriculum in their learning activities in the classroom using simplified learning materials, an equal teaching and learning process, adequate infrastructure and a safe, comfortable and child-friendly learning environment.